Derivative-free nonlinear optimization filter simplex - Correia, Aldina; Matias, Joáo; Mestre, Pedro; Serodio, Carlos (Zielona Góra: Uniwersytet Zielonogórski)
The filter method is a technique for solving nonlinear programming problems. The filter algorithm has two phases in each iteration. The first one reduces a measure of infeasibility, while in the second the objective function value is reduced. In real optimization problems, usually the objective function is not differentiable or its derivatives are unknown. In these cases it becomes essential to use optimization methods where the calculation of the derivatives or the verification of their existence is not necessary: direct search methods or derivative-free methods are examples of such techniques.
Keywords: nonlinear constrained optimization; filter methods; direct search methods